Molecular mimicry by Trypanosoma cruzi: the F1-160 epitope that mimics mammalian nerve can be mapped to a 12-amino acid peptide. - Van Voorhis, W C (1991)
Antigenic mimicry by Trypanosoma cruzi antigens that share epitopes with mammalian tissues may drive autoreactive B- or T-cell clones to expand and cause autoimmune pathogenesis. We have been studying one of these antigens, F1-160, a 160-kDa protein on the surface of T. cruzi that antigenically mimics a 48-kDa protein found in mammalian axonal and myenteric plexus cells. The F1-160 antigen has been characterized by cloning and expression of T. cruzi DNA encoding F1-160 in Escherichia coli. Recombinant peptides from various regions of the F1-160 gene were expressed and used to compete with affinity-purified polyclonal anti-F1-160 antibodies binding to nerve. Recombinant 48-amino acid peptide (48X) derived from expression of base pairs 611-761 of the DNA sequence completely inhibited anti-F1-160 binding to nerve. Recombinant peptides expressed from DNA lacking this region did not inhibit anti-F1-160 binding to nerve. Three peptides were synthesized to encompass the 48X peptide, a 12-amino acid peptide and two 18-amino acid peptides. The 12-amino acid peptide TPQRKTTEDRPQ (12X), corresponding to bases 615-651, completely inhibited the binding of anti-F1-160 antibodies to nerve at a concentration of 80 ng/ml (30 microM). The two 18-residue peptides did not inhibit, even at 10 micrograms/ml. Thus, the epitope of F1-160 crossreactive with nervous tissue can be mapped to a 12-amino acid peptide. Some humans with T. cruzi infection make antibodies to F1-160 and to the 48X and 12X peptides. Control sera from uninfected persons did not react with these antigens. Anti-48X antibodies, immunoselected from human serum with 48X peptide, bind to human nerve axons. This demonstrates that some individuals infected with T. cruzi make antibodies to the F1-160 epitope crossreactive with nervous tissues.